Suppressions and additions to the flora of the Juan Fernández archipelago (Chile). Issue 4 (2nd October 2017) - Danton, Philippe; Perrier, Christophe
ABSTRACT: Supplement to the Nouveau catalogue de la flore vasculaire de l'archipel Juan Fernández, Chili (Danton and Perrier 2006), this paper presents the taxa (61) that can be today removed from the list of the plants present in the archipelago and those (68) that must be added since the publication of our Nouveau catalogue.